Stomatal density, leaf area and plant size variation of Rhizophora mangle (Malpighiales: Rhizophoraceae) along a salinity gradient in the Mexican Caribbean - Peel, Joanne R.; Mandujano Sanchez, Maria C.; Lopez Portillo, Jorge; Golubov, Jordan (Revista de Biología Tropical, 2017)
In community ecology, the knowledge of abiotic factors, that determine intraspecific variability in ecophysiological and functional traits, is important for addressing major questions, such as plant community assembly and ecosystem functioning. Mangroves have several mechanisms of resistance to salinity and most species exhibit some xeromorphic features in order to conserve water. Leaf area and stomatal density play an important role in maintaining water balance, and gas exchange is regulated by their aperture and density, two traits that vary intraspecifically in response to environmental conditions, such as water stress and salinity. In this study, we evaluated the effects of salinity on stomatal density, leaf area and plant size in R. mangle and we tested for associations among the three variables, across three sites along a natural salinity gradient in the Xel-Há Park, Quintana Roo, Mexico. We hypothesized that high salinity sites would produce smaller plants, with smaller leaves, and fewer stomata. Three sampling sites with different environmental conditions were chosen and salinities were monitored monthly. A total of 542 plants were tagged and tree heights and diameters were measured for each individual within each of the three sampling sites. Three leaves from 20 trees from each site were measured to determine leaf area. Stomatal densities were determined in each leaf using nail polish casts, examining ten 1 mm squares per leaf under an optical microscope. A principal component analysis was used to assess association between tree height, leaf area, and stomatal density for each plot. The salinity gradient was reflected in plant size, producing smaller plants at the higher salinity site. The largest leaves were found at the low salinity site (51.2 ± 24.99 cm2). Leaf length was not correlated to plant size (LL vs. tree height: r= 0.02, P= 0.8205; LL vs. trunk diameter: r= 0.03, P= 0.7336), so we concluded that leaf length is an environmentally plastic trait of red mangroves that may vary as a function of environmental conditions, such as hydric stress caused by elevated salinity. The larger leaves from the low salinity site had lower densities of stomata (65.0 stomata.mm2 SD= 12.3), and increasing salinities did not decrease stomatal density (intermediate salinity site: 73.4 stomata.mm2 SD= 13.5; high salinity site: 74.8 stomata.mm2 SD= 17.3). Our results confirm that stomatal density is inversely related to leaf area (r= -0.29, P < 0.001), especially leaf width (r= -0.31, P < 0.001), and that salinity may increase stomatal density by causing reduction of leaf size.